Measurement of forward tt [bar], W+bb [bar] and W+cc [bar] production in pp collisions at √s=8TeV - Aaij, Roel; D'Argent, Philippe; Bachmann, Sebastian; Braun, Svende; Britsch, Markward; Comerma-Montells, Albert; De Cian, Michel; Esen, Sevda; Gerick, David; Gersabeck, Evelina; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (Physics letters, 2017)
The production of tt‾, W+bb‾ and W+cc‾ is studied in the forward region of proton-proton collisions collected at a centre-of-mass energy of 8 TeV by the LHCb experiment, corresponding to an integrated luminosity of 1.98±0.02 fb−1. The W bosons are reconstructed in the decays W→ℓν, where ℓ denotes muon or electron, while the b and c quarks are reconstructed as jets. All measured cross-sections are in agreement with next-to-leading-order Standard Model predictions.
LHCb Collaboration: R. Aaij, P. d’Argent, S. Bachmann, S. Braun, M. Britsch, A. Comerma-Montells, M. De Cian, S. Esen, D.Gerick, E. Gersabeck, X.Han, S. Hansmann-Menzemer, M. Kecke, B. Khanji, M. Kolpin, K. Kreplin, B. Leverington, J. Marks, M. Meissner, D.S. Mitzel, S. Neubert, M. Neuner, T. Nikodem, A. Piucci, M. Stahl, S. Stemmle, J. v. Tilburg, U. Uwer, M. Vesterinen, A. Zhelezov [und weitere]
Gesehen am 19.09.2018